Multilocus sequence typing of Ochrobactrum spp. isolated from gastric niche - Kulkarni, Girish; Gohil, Kushal; Misra, Vatsala; Kakrani, Arjun L.; Misra, Sri P.; Patole, Milind; Shouche, Yogesh; Dharne, Mahesh (Journal of infection and public health, 2017)
The human stomach is colonized by diverse bacterial species. The presence of non-Helicobacter pylori bacteria in urease-positive biopsies of individuals has been reported. Bacteria belonging to the Ochrobactrum genus have been documented in the human gastric niche. The co-occurrence of Ochrobactrum spp. with H. pylori was previously reported in an antral biopsy of a non-ulcer dyspeptic (NUD) subject from Northern India. There is no information on the genetic diversity of Ochrobactrum spp. isolated from the gastric niche in the stomach. We aimed to study the species distribution and diversity of Ochrobactrum spp. with and without H. pylori in urease-positive biopsies across three different geographical regions in India. Sixty-two Ochrobactrum isolates recovered from patients with an upper gastric disorder (n=218) were subjected to molecular identification and multilocus sequence typing. H. pylori DNA was found in the majority of biopsies, which had a variable degree of Ochrobactrum spp present. Interestingly, some of the urease-positive biopsies only had Ochrobactrum without any H. pylori DNA. Based on phylogenetic analysis, the Ochrobactrum isolates were distributed into the O. intermedium, O. anthropi and O. oryzae groups. This indicates there are multiple species in the gastric niche irrespective of the presence or absence of H. pylori. Antibiotyping based on colistin and polymyxin B could differentiate between O. intermedium and O. anthropi without revealing the resistance-driven diversity. Considering the prevalence of multiple Ochrobactrum spp. in the human gastric niche, it is important to evaluate the commensal and/or pathogenic nature of non-H. pylori bacteria with respect to their geographical distribution, lifestyle and nutrition needs.